STUDY OF THE PREVALENCE OF CHRONIC GASTROINTESTINAL DISEASES AMONG TMA STUDENTS (The Conference Hub, 2025)
Since the middle of the 20th century, human life has been accompanied by global changes in the health of the population in almost all countries of the world. Stress, information overload, the tension of everyday life, changes in the environment, nutrition, food production technology, physical inactivity have ultimately led to a widespread increase in the level of somatic diseases, their chronicity, and an increase in the number of people genetically predisposed to this pathology.